Dr. Mohammad Hoesin Hospitals Cancer Incidence: Hospital-Based Cancer Registration Data - Dewi, Citra; Dian Puspita; Sandria; Romi Ramkita (Jurnal RSMH Palembang, 2023)
Dr. Mohammad Hoesin Hospitals Cancer Incidence: Hospital-Based Cancer Registration Data. Cancer worldwide is summarized through a complex process called cancer registries. Based on data from the Global Burden of Cancer Study (GLOBOCAN), there will likely be approximately 10 million cancer-related deaths and 19.3 million new cases of cancer globally in 2020. However, Indonesia still does not have cancer incidence data based on population, as well as hospital-based cancer incidence data, especially the Dr. Mohammad Hoesin General Hospital Palembang, the main referral center for cancer in the South Sumatra region. This study aims to determine the distribution of cancer cases based on gender, age, organs, and cell origin in Dr. Mohammad Hoesin General Hospital Palembang for the period 2012-2019. This is an observational-descriptive study with 3413 samples taken from hospital cancer registry data, including topography, cell origin, age, and gender data from January 1, 2012, to December 31, 2019. The data is then processed and presented as distribution and frequency on tables and graphs using the SPSS application version 26. Cancer is prevalent in 63.5% of women and 36.5% of men. More than 53% of cases of cancer are diagnosed in the age range of 41-60 years. Acute lymphoblastic leukemia, infiltrating duct carcinoma, and adenocarcinoma are the most common cases of cancer in the age groups 0-20 years, 21-40 years, and >40 years, respectively. Based on location, breast, cervix-uteri, and colon occupy the 3rd highest position. By origin, 72% of cancer came from epithelial cells (carcinoma), 281 cases came from lymphoid cells (lymphoma), and 96 cases came from mesenchymal cells (sarcoma). Cancer generally occurs in females, patients aged 41-60 years, the most common location of the breast, and originates from epithelial cells (carcinoma).